SMART: software for advanced registration and visualization of human morphological, kinematics and motion data - Moiseev, F.; Sholukha, V.; Aranov, V.; van Sint Jan, S. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
This paper presents a software tool that allows real time registration for anatomically and biomechanically correct modeling of the human lower extremities. Automated registration of heterogenous data is performed: motion capture, electrogoniometry and computer tomography data. Interactive result adjustment is also available.